Reflections on the Italian Tax Judiciary System from the Perspective of the European Convention on Human Rights - Trenta, Cristina (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
EU law is applied uniformly in all EU Member States as a consequence of its supremacy in the hierarchy of legal sources. The same is not true of the European Convention on Human Rights (ECHR). This paper investigates the application of the ECHR principles of impartiality and independence of tax judges in the Italian tax judiciary system and specifically in relation to their role in Tax Commissions. Italy takes a dualistic approach that does not automatically give international law precedence over domestic law, even when international treaties are signed and ratified, causing compliance issues. The article identifies several crucial friction points between the current setup of the Italian tax judiciary system and the European Convention on Human Rights, most notably in respect to the principle of independency and impartiality of tax judges, and concludes suggesting that a reform in the field may be necessary. This paper was made possible by the financial assistance of the Torsten Söderbergs Stiftelse.